Determination of total polycyclic aromatic hydrocarbon (PAHs) in road dust along Kuantan-Gambang road - Nur Arifah , Jaafar (2012)
Polycyclic Aromatic Hydrocarbons , (PAHs) is a type of potential environments pollutants which consists of fused aromatic rings. PAHs do not contain heteroatoms or carry any substituents. Anthracene is one of the simplest examples of PAHs. PAHs are formed by incomplete combustion of carbon materials such as wood, coal, and diesel. PAils generated through combustion will emit to the ambient air as gases and particles. When the atmospheric PAils escaped the photo-degradation in the air, they will be accumulated to the land surface. In this study, road dust sample was collected along the Kuantan-Gambang road and the Polycyclic Aromatic Hydrocarbon (PAils) content then determined. Several main road lines in Kuantan-Gambang road were selected as sampling sites covering residential area, mining area, behind the FIST lab in UMP campus and etc. The samples were analyzed for the presence of total Polycyclic Aromatic Hydrocarbon (PAHs). Ultrasonic Agitation was used for the sample extraction. Next, the extracts were analyzed by UV-fluorescence spectrophotometer (Cary 50 Conc UV-Fluorescence Spectrophotometer Model) in order to determine the total PAHs at 254 nm excitation wavelength. The fluorescence intensities were measured at 360 nm, using crude oil solution as quantitative standard.